PROFIL KEMAMPUAN MAHASISWA CALON GURU BIOLOGI DALAM MENGOMUNIKASIKAN HASIL PRAKTIKUM FISIOLOGI HEWAN - Astuti, Yuni; Suciati, R. (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2017)
The main problem in this research is to analyze the profile communications skill of Biologyâ€™s student teachers in preparing the report practicum course on Animal Physiology. The research method used is descriptive quantitative method. Data (score of practical reports) is averaged then analyzed descriptively. The results are the ability of prospective biology teacher in communicating the practical results fall into the category enough and tends to increase. Mean score of practical report 1, 2, and 3 respectively 1.72; 2.03; Â 2.31. In addition, aspects of assessment